Alternative development an anthology - Mendis, D. L. O.; Rotblat, Joseph, 1908-2005.; Sri Lanka Pugwash Group (Colombo Sri Lanka Pugwash Group, 2005)
Includes papers presented at various Pugwash meetings.
Errata slip inserted in v. 1.
Keywords: Nuclear arms control; War -- Termination; Peace